1996
DOI: 10.1097/00006123-199603000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protein and Blood Cells on the Flow-pressure Characteristics of Shunts

Abstract: It has long been assumed that a high cerebrospinal fluid protein concentration adversely affects the performance of shunts. There is little experimental evidence to support this viewpoint, however, and the few reports that have been published can be criticized for poor experimental design or presentation of results. A flow-dependent shunt perfusion model was constructed. PS Medical Flow Control valves (PS Medical Corporation, Goleta, CA) and Cordis-Hakim valves (Cordis Corporates, Miami, FL) were perfused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
1
19
1
2
Order By: Relevance
“…16) We also believe that a washout period of red blood cells in CSF, which can cause shunt failure, is also desirable. 1,2) External drainage placement after aneurysmal surgery is often prolonged in our institute, which may induce bacterial colonization, 9) although we did not confirm any cases of meningitis in our study. It is advantageous to wait as long as possible for bacterial elimination before VP shunt implantation.…”
Section: Discussioncontrasting
confidence: 56%
“…16) We also believe that a washout period of red blood cells in CSF, which can cause shunt failure, is also desirable. 1,2) External drainage placement after aneurysmal surgery is often prolonged in our institute, which may induce bacterial colonization, 9) although we did not confirm any cases of meningitis in our study. It is advantageous to wait as long as possible for bacterial elimination before VP shunt implantation.…”
Section: Discussioncontrasting
confidence: 56%
“…(17) Such blood products can cause physical obstruction within the ventricular system and may lead to microscopic obstruction of the arachnoid granulations, thereby giving rise to hydrocephalus. (18,19) In summary, patients with good-grade aneurysmal SAH undergoing surgical clipping were 1.5 times more likely to have poor outcomes compared to those undergoing endovascular coiling, with an absolute difference of 5.2%. This group of patients was also 1.8 times more likely to require a VP shunt at the end of their six-month follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies mention biofilm or proteinaceous debris on the valve surface upon removal. 5,6,9,10,17 However, other studies analyzing protein counts in the CSF both in vitro and after complication have shown no significant correlation with shunt failure. 5,6,19 The increased technological Fig.…”
Section: 21mentioning
confidence: 99%
“…15,19 Authors have reported that protein level has no direct relationship to valve failure. [5][6][7]15,19 Using scanning electron microscopy, Brydon et al 5,6 reported that 13% of their 102 explanted valves studied after shunt failure were coated by white, red, or degenerating cells. Most were coated with protein, but the thin coating was not thought to be the cause of shunt failure.…”
mentioning
confidence: 99%